SAP and Partners: IS-H™ and IS-H*MED™ - Gell, G.; Schmücker, P.; Pedevilla, M.; Leitner, H.; Naumann, J.; Fuchs, H.; Pitz, H.; Köle, W. (Methods of Information in Medicine, 2003)
Objectives: The Styrian Hospital Organization with 21 hospitals including the Graz University Hospital, and the Heidelberg University Hospital implemented a new HIS based on SAP/R3™, ISH™, ISH*MED™ with the objective to have an integrated system to support patient administration and management, patient care, clinical documentation, research etc.Methods: Heidelberg University Hospital chose a step by step method for the introduction of the system, beginning with patient administration (ISH) and proceeding with clinical functions (ISH*MED). In Styria, the full functionality was implemented – as part of the selection process – in one peripheral hospital and in the Ear, Nose and Throat (ENT) Department of the Graz University Hospital, including special documents to support the processes in the highly specialized ENTunits.Results and Conclusions: The standard modules are performant, stable and basically well accepted. Particularly in Graz, it has been shown that the requirements of highly specialized departments for work flow management, documentation and integration of subsystems and data from different sources can be fulfilled by special documents and programs – although at the expense of additional workload particularly in the initial phases of such a project.
Keywords: Hospital information systems; electronic patient record